Pemanfaatan Pekarangan dan Teras Rumah di Tengah Kota Sebagai Suatu Kawasan Rumah Pangan Lestari (KRPL) - Kartanto, Kartanto; Djohar, Djohar; Rahmawati, Mariana Fitria; Afdah, Umi; Umanailo, Muhamad Chairul Basrun; Zarliani, Wa Ode Al (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2024)
The area of yards throughout Indonesia can reach 10.3 million hectares. The problem is that millions of hectares of this yard have not been utilized for optimal productivity business, so efforts are needed to optimize the yard and terrace land. This research aims to (1) socialize and invite the active participation of the Arjosari village community to create a sustainable food house area (KRPL); (2) design the KRPL model with the block model; (3) establish a sustainable environment group (KLL), (4) identify obstacles in the implementation of KRPL. Method The research was conducted in a participatory manner using 30 respondents in one Rukun Masyarakat (RW) area. The results showed that people in Arjosari Village, Blimbing District, Malang City are not difficult to invite to form a Sustainable Food House Area (KRPL), and the level of citizen participation in the KRPL program is quite high. Similarly, the KRPL design research with the Block model, it turns out it can accelerate the expansion of the KRPL program. Meanwhile, efforts to continue the KRPL program were formed by an institutional organization in the form of a Sustainable Environment Group (KLL).